A Systematic Review of Personalization Strategies in E-commerce: Examining their Impact on Customer Experience and Purchase Behavior - Nurdianasari, Rista; Md. Saad, Nor Hasliza (JURNAL BISNIS STRATEGI, 2025)
This systematic review examines the application of personalization strategies in e-commerce and their impact on customer experience and purchasing behavior. Drawing on 21 documents from the Scopus database, the review highlights the most pertinent strategies for product recommendations, user interface customization, and other advanced technologies, such as augmented reality (AR) and generative artificial intelligence (GENAI). The findings suggest that personalization enhances customer satisfaction, loyalty, and conversion rates; however, challenges like data privacy concerns, algorithmic bias, and implementation complexity persist. This review offers actionable insights for practitioners and identifies directions for future research, emphasizing ethical and scalable personalization practices to achieve optimal customer-centric outcomes.